Genetic overlap between autoimmune diseases and non-Hodgkin lymphoma subtypes - Din, Lennox; Sheikh, Mohammad; Kosaraju, Nikitha; Smedby, Karin Ekstrom; Bernatsky, Sasha; Berndt, Sonja I; Skibola, Christine F; Nieters, Alexandra; Wang, Sophia; McKay, James D; Cocco, Pierluigi; Maynadié, Marc; et al. (Genetic epidemiology, 2019)
Epidemiologic studies show an increased risk of non-Hodgkin lymphoma (NHL) in patients with autoimmune disease (AD), due to a combination of shared environmental factors and/or genetic factors, or a causative cascade: chronic inflammation/antigen-stimulation in one disease leads to another. Here we assess shared genetic risk in genome-wide-association-studies (GWAS). Secondary analysis of GWAS of NHL subtypes (chronic lymphocytic leukemia, diffuse large B-cell lymphoma, follicular lymphoma, and marginal zone lymphoma) and ADs (rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis). Shared genetic risk was assessed by (a) description of regional genetic of overlap, (b) polygenic risk score (PRS), (c)"diseasome", (d)meta-analysis. Descriptive analysis revealed few shared genetic factors between each AD and each NHL subtype. The PRS of ADs were not increased in NHL patients (nor vice versa). In the diseasome, NHLs shared more genetic etiology with ADs than solid cancers (p = .0041). A meta-analysis (combing AD with NHL) implicated genes of apoptosis and telomere length. This GWAS-based analysis four NHL subtypes and three ADs revealed few weakly-associated shared loci, explaining little total risk. This suggests common genetic variation, as assessed by GWAS in these sample sizes, may not be the primary explanation for the link between these ADs and NHLs.
Keywords: multifaktoriální dědičnost; autoimunitní nemoci; lidé; Middle Aged; HLA antigeny; Risk Factors; Polymorphism, Single Nucleotide; Female; nehodgkinský lymfom; jednonukleotidový polymorfismus; Humans; Autoimmune Diseases; HLA Antigens; Multifactorial Inheritance; lidé středního věku; mužské pohlaví; genetická predispozice k nemoci; ženské pohlaví; Alleles; Lymphoma, Non-Hodgkin; Male; alely; Genetic Predisposition to Disease; rizikové faktory